Perkembangan Pemikiran Tasawuf Dari Periode Klasik Modern Dan Kontemporer - Hadiat; Rinda Fauzian (SALIHA: Jurnal Pendidikan & Agama Islam, 2022)
The practice of Sufism in the field is very diverse and extraordinary for the expansion of Islamic treasures. This shows that the development of the practice of Sufism is very massive from time to time. The purpose of this study is to describe the development of Sufism thought from time to time, so that the striking differences can be understood by all. The research method used is library research method. The results of the study show that Sufism developed based on the phases of thought and wordview that occurred at that time. The stages of development include: first, the formation period. This period has been since the second decade of Hijriyah by prioritizing asceticism. Second, the development period. At this time Sufism developed in the 3rd century H which saw a concrete transition from asceticism to Sufism. Third, the consolidation period. This period emerged in the 5th century H, which was a time of struggle between the age of asceticism and the development period with the face of Sufism. Fourth, the philosophical period. At this time, it was based on the integration of Sufism and philosophy theories. Fifth, the period of purification. This period is a time of purification from matters related to heresy and superstition